Calcineurin–NFAT signalling in myeloid leucocytes: new prospects and pitfalls in immunosuppressive therapy. Issue 8 (12th June 2017) - Bendickova, Kamila; Tidu, Federico; Fric, Jan
Abstract: Myeloid leucocytes mediate host protection against infection and critically regulate inflammatory responses in body tissues. Pattern recognition receptor signalling is crucial for myeloid cell responses to pathogens, but growing evidence suggests an equally potent role for Calcineurin–NFAT signalling in control of myeloid cell function. All major subsets of myeloid leucocytes employ Calcineurin–NFAT signalling during immune responses to pathogens and/or tissue damage, but the influence this pathway exerts on pathogen clearance and host susceptibility to infection is not fully understood. Recent data from experimental models indicate that Calcineurin‐NFAT signalling is essential for infection control, and calcineurin inhibitors used in transplantation medicine (including cyclosporine A and tacrolimus) are now being tested for efficacy in a diverse range of inflammatory conditions and autoimmune pathologies. Efforts to repurpose calcineurin inhibitor drugs for new therapeutic applications may yield rapid improvements in clinical outcomes, but the potential impact of these compounds on myeloid cell function in treated patients is largely unknown. Here we discuss Calcineurin–NFAT control of myeloid leucocyte function in the context of recent therapeutic developments and ongoing clinical studies. Abstract : This review summarises our current knowledge on calcineurin‐NFAT in innate immune responses and discusses the use of calcineurin inhibitors known in transplantation medicine for autoimmune pathologies and inflammatory disorders.